Sistema agroalimentario del maíz blanco en Ciudad Arce, municipio de El Salvador - Ayala Durán, Carlos Ernesto (2018)
Aiming to understand interrelations surrounding maize culture in El Salvador, the present work addresses white maize agri food system in Ciudad Arce. To do so, this thesis has used localized agrifood systems as theoretical framework. Thereof, historical, technical, institutional and food aspects compounding the localized agrifood system have been studied. Seemingly, this thesis has carried out a dense fieldwork, spreading through direct interviews with 82 maize producers in Ciudad Arce. Additionally, a number of actors, both public and private, have been interviewed, including: Rural extentionists, researchers, inputs providers, food retailers among others. This thesis begins with a theoretical analysis of territory. Thereof, the territorial perspective developed in the present work has been enriched from Geography, since it was originally within this science where territory emerged and where it has been more rigorously studied. This theoretical discussion of territory has paved the way to analyze its appropriation by productive agglomeration approaches such as: Industrial districts, clusters, local productive arrangements, local productive systems, rural agoindustry and localized agrifood systems. Given our above mentioned analysis on territory, it is highlighted that all these theoretical perspectives conceive the territorial concept with a positive bias, leaving aside the historical power relations accompanying territory from a geographical perspective. Subsequently, and given a lack of detailed and trustworthy statistics and databases in El Salvador, this thesis profoundly describes maize producers in Ciudad Arce. To do so, the framework of localized agrifood systems is implemented, describing producers in terms of their historical, technical, institutional and food peculiarities. This characterization paved the way to conceptualize and analyze how the maize localized agrifood system is structured in Ciudad Arce. Besides this conceptualization and analysis, the present work has exposed power relations at different levels, some of which are not conscripted to the usual economic and political arena. Hence, it has been possible to identify and discuss at least two power relations in each of the four dimensions that form the above mentioned localized agrifood system (LAFS). This qualitative analysis set the way to move onto a quantitative discussion. Within it, a system of four regressions (one for each LAFS dimension) was performed to predict and quantify maize productivity variations. Likewise a system of four regressions was used to predict and quantify variations in total production of this cereal. In general terms, regressions having productivity as dependent variable showed more modest results. Afterwards, another multiple regression was used to predict the variations of maize production including variables from all four different dimensions form the LAFS. At this point selected variables were combined into only one multiple regression in order to integrate the previous isolated dimensions. This regression was able to predict 83% of variations in maize production (R²: 0.830/ R² Adjusted: 0.782). These results identified many variables that influence total production, among the three most relevant in decreasing importance are: Area planted, commercial motivation to produce maize and the possession of an irrigation system. At the end, this thesis elaborates final considerations at both theoretical and practical level. Likewise, it also points to new research lines.